Combining Photometry from Kepler and TESS to Improve Short-period Exoplanet Characterization. (13th June 2016) - Placek, Ben; Knuth, Kevin H.; Angerhausen, Daniel
Abstract: Planets emit thermal radiation and reflect incident light that they receive from their host stars. As a planet orbits its host star the photometric variations associated with these two effects produce very similar phase curves. If observed through only a single bandpass, this leads to a degeneracy between certain planetary parameters that hinder the precise characterization of such planets. However, observing the same planet through two different bandpasses gives much more information about the planet. Here we develop a Bayesian methodology for combining photometry from both Kepler and the Transiting Exoplanet Survey Satellite . In addition, we demonstrate via simulations that one can disentangle the reflected and thermally emitted light from the atmosphere of a hot-Jupiter as well as more precisely constrain both the geometric albedo and day-side temperature of the planet. This methodology can further be employed using various combinations of photometry from the James Webb Space Telescope, the Characterizing ExOplanet Satellite, or the PLATO mission.